Management of ureteral obstruction in crossed fused renal ectopia: A case report - Bhojwani, Nicholas; Hartman, Jason Brett; Ahmed, Manzoor; Morgan, Robert; Davidson, Jon C (Canadian Urological Association Journal, 2014)
Crossed fused renal ectopia is a rare congenital malformation. We describe a case in which a 58-year-old male with left-sided crossed fused renal ectopia presented with urinary bladder outlet obstruction due to metastatic prostate adenocarcinoma. Glomerular filtration rate (GFR) was 13 mL/min, creatinine 4 mg/dL, and blood urea nitrogen (BUN) 58 mg/dL. The patient underwent successful image-guided placement of percutaneous nephrostomy tubes which were later converted to nephroureteral stents. Labs improved to a GFR of 28 mL/min, creatinine of 2.4 mg/dL, and BUN of 41 mg/dL. In this case standard image-guided renal decompression techniques were effective in treating a patient with crossed fused renal ectopia.